Manufacturing sector and economic growth in South Africa : a Time Series Test of Kaldor’s First Growth Law - Mongale, I. P.; Tafadzwa, M. (International Conference on Public Administration and Development Alternatives, 2018)
Recently, South Africa has experienced a slow economic growth coupled with population growth outpacing economic growth. To curb the socio-economic problems brought by this situation, more, better and sustainable jobs need to be generated. According to 'engine of growth' hypothesis, the manufacturing sector is touted as an important sector in this regard but it was found out that matched with other economic sectors this sector is not performing well in South Africa. Given the limited amount of literature available on this is issue, it is the intention of this study to contribute to this research gap by investigating the relationship between the manufacturing sector and economic growth in order to test Kaldor’s first growth law in South Africa. As contribution to literature, this paper employed the Vector Error Correction to estimate the annual time series data from 1980 to 2016 obtained from World Bank. The empirical investigation revealed that manufacturing sector proxied by the manufacturing output has a positive and significant coefficient which confirmations that the sector contributes positively towards economic growth. The study recommends that the South African policy makers should consider advocating for strengthening and promoting this sector. Policies should be geared towards creating the environment which is more conducive for business expansion and investing in capital formation which will allow more job creation. Keywords: Economic growth, Manufacturing sector, South Africa, Vector error correction model
Journal Article Published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Economic growth; Manufacturing sector; South Africa; Vector error correction model; Endogenous growth (Economics); Economic development